Flexural behavior of composite sandwich panel of aluminum foam and epoxy resin. Issue 2 (23rd October 2017) - Cheng, Shuliang; Zhao, Xuya; Liu, Xiaoman; Yu, Wei; Xin, Yajun
Abstract : The mechanical properties in bending tests of an integrated composite sandwich panel of aluminum foam and epoxy resin were studied through quasi-static four-point bending tests. The failure modes and typical force–cross-head curves were obtained. The bending rigidity, energy absorption capacity and flexural bearing capacity of the panel were analyzed compared to those of the traditional sandwich panel. The test results indicate that this kind of composite sandwich panel has good integrality and stability. The typical force–cross-head displacement curves present three phases: elastic phase, strengthening phase and destruction phase. The flexural rigidity, energy absorption capacity and flexural bearing capacity are affected by composite layer thickness and specimen thickness, and the specimen with a composite layer of 2·5 mm has the optimal behavior. The mechanical properties of the integrated composite sandwich panel have been highly improved compared with those of the traditional sandwich panel. The specimens maintain good stability under bending, and no peeling-off or cracking appears between the composite layer and core.